Illustration of 'The German Embassy in the Rue de Lille' France in the... - Washburne | E. B.... (Wikimedia Commons, 1887)
Notice iconographique issue de Wikimedia Commons. Titre: Illustration of "The German Embassy in the Rue de Lille" France in the 1870s (cropped). The metadata below describe the original scanning. Follow the "All Files: HTTP" link in the "View the book" box to the left to find XML files that contain more metadata about the original images and the derived formats (OCR results, PDF etc.). See also the https://archive.org/about/faqs.php#140 " rel="nofollow">What is the directory structure for the texts? FAQ for information about file content and naming conventions. Subjects: Washburne, E. B. (Elihu Benjamin), 1816-1887 | Franco-Prussian War, 1870-1871 | Diplomats | Diplomats
Droits : Licence Public domain via Wikimedia Commons
Keywords: iconographie; illustration; gravure; patrimoine; wikimedia commons; Iconographie